Sociodemographic-food characterization and the carbon footprint of the diet of Mexican adults during the COVID-19 pandemic - Kala Saldaña, Axel Roberto; Espinosa Ayala, Enrique; Márquez Molina, Ofelia (Revista Chapingo Serie Agricultura Tropical, 2022)
The environmental impact of human activities negatively influences the ecosystem balance, and food production systems are the cause of up to 30% of greenhouse gas (GHG) emissions. The consumption of food products that precedes this production chain is influenced by various social, cultural, and economic factors, such as the current COVID-19 pandemic, which, through home quarantine, affects behavioral, cognitive, and physiological processes of people. The objective of this research was to analyze the sociodemographic characteristics of eating patterns and their CO2 emission in a sample of Mexican adults before, during, and after the home confinement due to coronavirus. The data was obtained through an electronic survey that included an adaptation of the Food Consumption Frequency of Teenagers and Adults, which was distributed through the main social networks, obtaining a total of 1 114 surveys. Subsequently, the dietary patterns and their carbon dioxide emission were determined. A variation in the intake of different food products and their carbon footprint was identified according to the sociodemographic qualities of the population and the confinement analysis times, analyzed by sections and conglomerates. It was found that the demographic properties of the sample and the Home Confinement by the COVID-19 (HCCOVID-19) are factors in the dietary diversity and its CO2 emission.